2018
DOI: 10.3906/sag-1701-86
|View full text |Cite
|
Sign up to set email alerts
|

In vivo attenuation of angiogenesis in hepatocellular carcinoma by Nigella sativa

Abstract: Background/aim: Angiogenesis is imperative in malignant tumor growth. Hepatocellular carcinoma is a typical hypervascular tumor that relies on angiogenesis. The aim of this study is to investigate the in vivo molecular mechanism underlying the antitumor properties of Nigella sativa ethanolic extract (NSEE) through its antiangiogenic effect against diethyl nitrosamine (DENA)-induced hepatocarcinogenesis. Materials and methods: Male Wistar rats were divided into 4 groups: normal, NSEE, DENA, and NSEE-DENA groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…Chronic inflammation has been implicated in various chronic illnesses [(cancer, cardiovascular disorders, diabetes, Alzheimer's disease, epilepsy, amyotrophic lateral sclerosis, rheumatoid arthritis, and asthma) that involve progressive and irreversible damage to the cell and/or neurons] as well as in many infectious conditions [99, 100]. Therefore, the crucial role of anti-inflammatory actions of different N. sativa preparations and TQ might be the possible sources for the development of a new generation of anti-inflammatory agent to treat these wide ranging conditions.…”
Section: Pharmacological Activities Of Nigella Sativamentioning
confidence: 99%
“…Chronic inflammation has been implicated in various chronic illnesses [(cancer, cardiovascular disorders, diabetes, Alzheimer's disease, epilepsy, amyotrophic lateral sclerosis, rheumatoid arthritis, and asthma) that involve progressive and irreversible damage to the cell and/or neurons] as well as in many infectious conditions [99, 100]. Therefore, the crucial role of anti-inflammatory actions of different N. sativa preparations and TQ might be the possible sources for the development of a new generation of anti-inflammatory agent to treat these wide ranging conditions.…”
Section: Pharmacological Activities Of Nigella Sativamentioning
confidence: 99%
“…VEGF is one of the best‐supported angiogenesis signaling pathways identified as positive regulators and is a selective cytokine which acts only on vascular endothelial cells. The level of VEGF correlated with the clinical course of the disease in various tumor tips .…”
Section: Introductionmentioning
confidence: 99%
“…The VEGF family is a significant target of antiangiogenic agents. VEGF released from extracellular matrix chiefly targets endothelial cells and is produced by cancer cells to mediate angiogenesis and metastasis of tumor cells …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our scRNA-seq data, we found BDL-6 hepatocytes were also involved in these processes. Angiogenesis, the sprouting of new vessels from preexisting ones, is an essential pathophysiological process required for embryogenesis, growth, regeneration, and wound healing [40]. It has been reported that liver injury and pathological angiogenesis are interdependent processes that occur in parallel.…”
Section: Discussionmentioning
confidence: 99%